Omental Torsion and Infarction Depicted by Ultrasound and Computed Tomography: An Unusual Cause of Abdominal Pain - Doganay, Selim; Gul, Yeliz; Kocakoc, Ercan (Japan Soc Internal Medicine, 2010)
[Abstract Not Available]
Keywords: omental torsion; infarction; computed tomography